Pengaruh Variabilitas Gerak Semu Matahari Terhadap Perubahan Waktu Salat Diberbagai Garis Lintang Perspektif Ilmu Falak - Sahrani, Nurul; Syarif, Rasyawan; Rahmatiah HL (HISABUNA: Jurnal Ilmu Falak, 2024)
“The sun is in apparent or phantom motion but it is the earth that moves around the sun. Prayer times are influenced by the length of day and night in each latitude or region. This study uses library research using qualitative research with descriptive analysis. Using Shar'i and astronomical aproaches. The resuls of this study indicate that the sun performs pseudo-motion. The apparent motion of the sun causes the rotation and revolution of the earth, so that the sun is north and south of the earth. The sun is north of the equator (around March 21 - September 23) and south of the equator (around September 24 - March 20). This causes the length of day and night and differences in prayer times in each region or latitude. For example, in Gowa the duhur prayer time is at 12:05, while in Manado it is at 12:23. But in December, the noon prayer time in Gowa is at 12:02, while in Manado it is at 11:50. Apart from the influence of the apparent motion of the sun, the latitude of the place also affects the change in prayer time. In falak science, the determination of prayer times is significantly studied in the form of formulas using data on the latitude of the place, solar declination, longitude, mean time, and sun height”. Keywords: Sun's Apparent Motion, Prayer Time, Latitude